AMINA WADUD MUHSIN GENDER THINKING IN THE HERMENEUTIC PERSPECTIVE OF HANS GEORG GADAMER - Muh. Yasin Yasin Nur; Indo Santalia; Muhaemin Latif (International Journal of Islamic Studies, 2021)
The purpose of this study is to find out the gender thinking of Amina Wadud Muhsin in the view of Hans Georg Gadamer's Hermeneutics. This research is library research using a research approach, namely: philosophical, grammatical, linguistic and phenomenological approaches. Then the source of this research data is taken from books, articles and journals related to the thoughts of Amina Wadud with Gadamer. Furthermore, the data analysis method used is descriptive method, content analysis, interpretation method, comparison, taxonomy. The results of this study indicate that: First, related to Amina Wadud's gender thinking, namely: 1. The creation of humans. According to Amina Wadud that the origin of humans, both male and female, comes from one nafs which is part of the paired system. 2. Leader. Amina Wadud strongly rejected Qawwamun to be limited to the position of men compared to women. However, there must be harmony, so Amina Wadud proposes a new idea, namely the "functionalist" concept. 3. Polygamy. For Amina Wadud, the concept of polygamy is not supported in religion, because there is no justice for women. Amina's gender thinking in the perspective of Hans Georg Gadamer's hermeneutics, in this case the interpreter's position. Amina Wadud places great emphasis on text priors and context. In this case the prior text concerns the background of an interpreter, his views and circumstances. Because an interpreter must dialogue with the text in accordance with any conditions and at any time. Likewise with Gadamer, the concept of language is the most important. This is what Gadamer calls "the influence of history".